CLINICAL PROFILE OF PATIENTS ATTENDING A PRISON PSYCHIATRIC CLINIC - Chadda, R.K. (Medknow Publications, 1998)
Psychiatric morbidity is higher in prison inmates as compared to that in general population but treatment facilities are often inadequate. The present work reports the profile of psychiatric patients seen in a jail hospital over a period of three months. The jail had about 9000 inmates. Psychiatric services consisted of weekly visit by a psychiatrist. Seventy two male inmates were seen during the period of study. Most of them (80%) were undertrials. Diagnosis included schizophrenia, depression, bipolar disorder, anxiety disorders, and malingering. Stress of imprisonment contributed to the illness only in a small percentage of patients. Among the admitted patients, jail environment interfered with improvement. Frequent relapses were noted among the improved schizophrenic patients when transferred back to the jail. The study emphasises the need for improving the conditions in jail and developing prison psychiatric units to be managed by psychiatrists.